Ukrainian energy sector: ecological and economic features (Economics and region, 2018)
The paper devoted to the main features of energy sector in Ukraine. Thus, the authors analysed the main energy resources which dominated in Ukraine. The results of analysing showed that the energy consumption has the season fluctuating. In addition, the findings approved that thermal power stations which used coal are the most polluters among energy companies. That is why it is necessary to reorient the energy market from the traditional resources to the renewable energy direction. In this case, changing of ecological tax system could be one of the incentive instruments to spread renewable energy. Besides, the authors proposed to include the assessment of environmental damage and season fluctuating from the using the traditional energy resources (coal, natural gas and etc.).
Keywords: ecological oriented development; energy sector; environment; fuel; renewable energy resources